2018
DOI: 10.13031/trans.12361
|View full text |Cite
|
Sign up to set email alerts
|

Design and Testing of a Kiwifruit Harvester End-Effector

Abstract: Abstract. Mechanisms to aid fruit harvesting are undergoing constant development with increasing available technologies. However, fruits grown on vines, such as kiwifruit, have complex tree architectures and present difficulties in confirming design parameters. The objective of this research was to develop an end-effector for a kiwifruit harvester based on integrating the physical characteristics of the fruit, such as stem length, the space between mature fruits, and the growing environment provided by a trell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Figure 5(b) shows that there is an approximate linear relationship between actual values and predicted values, which indicated the established model had a high prediction accuracy for ESGA. The final equations of the mathematical model of the ESGA are shown in equation (1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5(b) shows that there is an approximate linear relationship between actual values and predicted values, which indicated the established model had a high prediction accuracy for ESGA. The final equations of the mathematical model of the ESGA are shown in equation (1).…”
Section: Resultsmentioning
confidence: 99%
“…With the decrease of the labor force and the corresponding increase of production costs, robotic picking has gradually become a hotspot in the agricultural field. 1,2 Fruit harvesting with high success rate is one of the key techniques of robotic harvesting, which is not only related to the branch-stem characteristics and harvesting strategy, but also largely depends on the structure of the end-effector. 3,4 Xie et al found that the optimal combination of harvesting parameters with the minimum separation force of the cherry tomato harvesting at the calyx/fruit joint was obtained in the pulling pattern.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the development of flexible materials, such as polydimethicone 6 and hydrogel, 7 and so forth, has promoted the flexible grippers, facilitating 'human-like' contact sensing and picking effects. 8 However, noteworthy literature on the endeffector primarily focuses on the structural design of the gripper, [9][10][11] where the biomechanics of fruit and the force interactions between the fruit and gripper are usually treated with simple compression contact. At present, the fruit crushing load obtained by macroscopic mechanical test is often used as the operating threshold of the end-effector, 12 which in fact may not be consistent with the microscopic damage threshold, potentially resulting in fruit breakage or damage.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Chinese sweet pepper production ranks first in the world (Shi et al, 2017). Picking is considered to be the most labor-intensive task in agricultural production (Li et al, 2008;Graham et al, 2018). The replacement of manual picking by robots has become a recent trend (Chen et al, 2019) following the popularization of agricultural technology (Kondo et al, 2009), the gradual reduction of rural labor and other related factors (Fan et al, 2016;Bac et al, 2017).…”
Section: Introductionmentioning
confidence: 99%